Cognitive styles and psi: psi researchers are more similar to skeptics than to lay believers - Pehlivanova, Marieta; Weiler, Marina; Greyson, Bruce (Frontiers in Psychology, 2024)
Introduction Belief in psi, which includes psychic phenomena such as extra-sensory perception and post-mortem survival, is widespread yet controversial. According to one of the leading and perhaps most tested hypotheses, high belief in psi can be explained by differences in various aspects of cognition, including cognitive styles. Most of this research has been conducted with lay individuals. Here, we tested the hypothesis that academic researchers who investigate psi may exhibit different cognitive styles than lay individuals interested in psi, and are more similar to skeptics. Methods We measured two cognitive styles—actively open-minded thinking (AOT) and the need for closure (NFC)—and assessed differences among four heterogeneous groups regarding belief in psi and involvement in related research. Specifically, our study included academic psi researchers (N = 44), lay individuals who believe in psi (N = 32), academics who are skeptics of psi (N = 35), and lay individuals who are skeptics (N = 33). Results We found group differences in AOT (p = 0.003) but not in NFC scores (p = 0.67). Post hoc tests showed no significant difference in AOT scores between academics who conduct psi research (4.5 ± 0.3) and academic skeptics (4.5 ± 0.3; p = 0.91) or lay skeptics (4.5 ± 0.4; p = 0.80). The lay psi group had significantly lower AOT scores (4.2 ± 0.4) than the other three groups (ps: 0.005–0.04), indicating a decreased willingness to consider a range of evidence when forming an opinion, including evidence that challenges their beliefs. AOT was negatively associated with psi belief in the two skeptic groups combined (r = −0.29, p = 0.01), but not in the psi groups (r = −0.03, p = 0.78). Discussion Our research shows that academics who work with psi differ from lay psi individuals, but not from skeptics, in actively open-minded thinking. In other words, despite their high belief in psi phenomena, psi researchers demonstrate a commitment to sound reasoning about evidence that is no different from that of skeptics.